2020
DOI: 10.1038/s41586-020-2714-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic control of intranuclear polarity by human cytomegalovirus

Abstract: Despite its size and rigidity, the nucleus is moved or reorganized by cytoskeletal filaments under various conditions 1 – 11 . Moreover, while chromatin organize into non-random domains 12 , extensive heterogeneity at the single-cell level 13 means that precisely how and why nuclei reorganize remains an area of intense investigation. Here, we developed convolutional neural network (CNN)-based automated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…For single cell RFP and GFP intensity measurements, randomized images were entered into the CellProfiler pipeline ( McQuin et al, 2018 ; Procter et al, 2020 ) and resized to 256×256 pixels. The pipeline was used to identify target objects using the images in the RFP channel.…”
Section: Methodsmentioning
confidence: 99%
“…For single cell RFP and GFP intensity measurements, randomized images were entered into the CellProfiler pipeline ( McQuin et al, 2018 ; Procter et al, 2020 ) and resized to 256×256 pixels. The pipeline was used to identify target objects using the images in the RFP channel.…”
Section: Methodsmentioning
confidence: 99%
“…These proteins do not directly bind the MIE locus, but rather they impart their effects through upstream control. Furthermore, recent findings suggest HCMV reorganizes inactive histones and cellular DNA, thereby isolating the viral genome to optimize viral gene transcription and replication [254]. Collectively, these suggest the cellular environment plays a large role in controlling MIE-mediated transcription and therefore the stage of infection.…”
Section: Cellular and Viral Factors Involved In Regulating The Mie Locusmentioning
confidence: 98%
“…As viruses have evolved with their hosts for thousands of years, examining how they either utilize or avoid cellular factors to promote infection has often been the basis of new scientific knowledge and discovery. In these two papers, Procter et al demonstrate just that through their investigation of how another important human pathogen, human cytomegalovirus (HCMV), manipulates the cell during infection ( 1 , 2 ).…”
Section: Commentarymentioning
confidence: 99%
“…In order to further investigate this virus-induced phenomenon, Procter et al ( 2 ) developed convolutional neural network (CNN)-based automated cell classification and analysis pipelines to measure the spatial organization of thousands of individual cells. The authors found that acetylated MTs generated at the viral AC interact with linker of nucleoskeleton and cytoskeleton (LINC) complexes in the nuclear membrane to rotate the nucleus through cytoplasmic dynein motor binding domains in Nesprin-2.…”
Section: Commentarymentioning
confidence: 99%